Free convection flow of a heterogeneous mixture of water and nano-encapsulated phase change particle (NEPCP) in enclosure subject to rotation. (July 2022) - Alhashash, Abeer; Saleh, Habibis
Abstract: Free convective heat transfer in hybrid nanofluids inside differentially heated square enclosure is considered. The square enclosure executes a steady uniform counterclockwise angular velocity about its longitudinal. The enclosure was filled with a heterogeneous mixture of base fluid and nano-encapsulated phase change particle (NEPCP). The NEPCP core can absorb thermal energy on charging state or releases energy on discharging state. The governing equations are solved using the using FEM. The validity of the present code is verified by comparing its predictions to the results form literature. The main outcomes is that the rotation parameter affects the cell circulation number, number of inner vortices and its intensity. Using higher speed of rotation leads to less NEPCP undergoes phase change and retard heat transfer. Graphical abstract: Highlights: Convection of a rotating enclosure filled with a suspension of water and NEPCP is addressed. The NEPCP core absorb thermal energy on charging state or releases energy on discharging state. Number of the peak heat transfer are sensitive to the laten heat. Using higher speed of rotation leads to less NEPCP undergo phase change.